Respuesta :
1. a = 3, b = -6, of the standard form.
Rewrite the equation to the vertex form will solve both 2 and 3:
3x^2 - 6x + 13 = 3(x^2 - 2x) + 13 = 3(x^2 - 2x + 1) + 13 + 3 = 3(x - 1)^2 + 16.
where the vertex (h,k) is (1, 16).
Rewrite the equation to the vertex form will solve both 2 and 3:
3x^2 - 6x + 13 = 3(x^2 - 2x) + 13 = 3(x^2 - 2x + 1) + 13 + 3 = 3(x - 1)^2 + 16.
where the vertex (h,k) is (1, 16).
The vertex of the equation is (1, 10), and values of a, b are 3 and 10 after comparing with the standard equation.
What is a parabola?
It is defined as the graph of a quadratic function that has something bowl-shaped.
We have a parabola equation:
f(x) = 3x² -6x + 13
On comparing with standard equation:
a = 3 and b = -6
f(x) can be written as:
f(x) = 3(x - 1)² + 10
Vertex: (1, 10)
Plug x = 1 in the function:
f(1) = 3(1 - 1)² + 10 = 10
Thus, the vertex of the equation is (1, 10), and values of a, b are 3 and 10 after comparing with the standard equation.
Learn more about the parabola here:
brainly.com/question/8708520
#SPJ2